Fusion of PDGFRB to MPRIP, CPSF6, and GOLGB1 in three patients with eosinophilia-associated myeloproliferative neoplasms - Naumann, Nicole; Schwaab, Juliana; Metzgeroth, Georgia; Jawhar, Mohamad; Dietz, Christian; Hofmann, Wolf-Karsten; Reiter, Andreas; Fabarius, Alice (Genes, chromosomes & cancer, 2015)
In eosinophilia-associated myeloproliferative neoplasms (MPN-eo), constitutive activation of protein tyrosine kinases (TK) as consequence of translocations, inversions, or insertions and creation of TK fusion genes is recurrently observed. The most commonly involved TK and their potential TK inhibitors include PDGFRA at 4q12 or PDGFRB at 5q33 (imatinib), FGFR1 at 8p11 (ponatinib), and JAK2 at 9p24 (ruxolitinib). We here report the identification of three new PDGFRB fusion genes in three male MPN-eo patients: MPRIP-PDGFRB in a case with t(5;17)(q33;p11), CPSF6-PDGFRB in a case with t(5;12)(q33;q15), and GOLGB1-PDGFRB in a case with t(3;5)(q13;q33). The fusion proteins identified by 5′-rapid amplification of cDNA ends polymerase chain reaction (PCR) or DNA-based long distance inverse PCR are predicted to contain the TK domain of PDGFRB. The partner genes contain domains like coiled-coil structures, which are likely to cause dimerization and activation of the TK. In all patients, imatinib induced rapid and durable complete remissions. © 2015 Wiley Periodicals, Inc.